Dual performance of business model innovation in emerging market enterprises: A configurational approach - Feifei Huang; Xingwu Luo; Mimi Xiao; Wenhao Dong (Journal of Innovation & Knowledge, 2025)
Business model innovation (BMI) is a critical driver of enterprise growth, yet its implementation in emerging market enterprises (EMEs) remains underexplored. To bridge this gap, our study adopts a configurational approach to systematically investigate the complex causal relationships among thematic BMI, strategic orientations, and environmental characteristics, while considering the dual performance imperatives—substantive and symbolic—of EMEs. Using fuzzy-set qualitative comparative analysis on EMEs from China, we reveal three key findings: (1) Pioneering and perfecting BMI operates through distinct mechanisms. Pioneering BMI enhances substantive performance by fostering differentiation advantages, whereas perfecting BMI improves symbolic performance by refining existing models to better meet articulated customer needs. (2) In pursuing dual performance outcomes, pioneering and perfecting BMI are mutually reinforcing. Their synergistic integration is essential for achieving dual performance objectives. (3) Dual BMI alone is insufficient to realize dual performance. Instead, alignment with strategic orientation and environmental characteristics is essential. Specifically, the synergy of digital orientation enhances firms’ substantive performance, whereas the interplay of policy orientation and environmental munificence enhances symbolic performance.